PELATIHAN PENCATATAN BIAYA BAHAN BAKU UNTUK MENINGKATKAN KINERJA KEUANGAN UMKM IKAN HIAS : The Training for Recording of Raw Material Costs to Improve the Financial Performance of UMKM Ornamental Fish - Raymond Raymond; Dian Lestari Siregar; Anggia Dasa Putri; Mohamad Gita Indrawan; Rio rahmat Yusran (PUAN INDONESIA, 2023)
This community service is carried out with the aim of increasing the knowledge and insight of small ornamental fish entrepreneurs at Perum Permata Hijau Block D, Bukit Tempayan Village, Batu Aji District, Batam City regarding the importance of recording raw material costs and business profit and loss reports to improve the financial performance of small businesses. The methods applied in this training are lectures, tutorials, and discussions. The lecture method is carried out by providing an overview and motivation about the importance of accounting for business. This coaching activity will be carried out over four meetings where the output of this activity is that the business can make financial reports containing methods of journalizing, balance sheet, recording of raw materials, profit and loss statements, and changes in business capital aimed at facilitating business activities.